Features and management of asynchronies in children - Lonero, Margherita; Di Nardo, Matteo (Pediatric Medicine; Vol 2 (September 2019): Pediatric Medicine, 2019)
Asynchronies during mechanical ventilation (MV) occur in case of absence of synchronization between the patient and the ventilator in terms of breath delivery timing. Children present different types of asynchronies and their management differs accordingly. Some pediatric peculiarities such as the high respiratory rate, the use of uncuffed endotracheal tubes and consequently air leakages may increase the occurrence of certain types of asynchronies. Unfortunately, the use of the standard ventilator waveforms (airway pressure-time and flow-time) to detect asynchronies is often not sufficient and needs to be integrated with other advanced monitoring tools. The objective of this review is to present the main pediatric asynchronies and their management.